(untitled) (Research, Society and Development, 2018)
This qualitative study investigated through a case study in public high schools in a Regional Superintendent of Education from Minas Gerais State, relationships between teacher´s view of their initial training and their role as a basic education teachers, with respect to the contents of Geometrical Optics and experimental activities. Ten teachers from six schools in five cities from a group of 29 teachers from 22 schools in 16 municipalities that comprised the jurisdiction of Superintendence were selected. The data were obtained through questionnaires with closed and open questions, which in a first part characterized the profile of the respondents, and in a second part interrelated to the geometric optics and the training and teaching performance. The results indicate that the group of teachers, though most of them do not have access to this content formally in initial training courses and they did not perform experimental activities, attach great importance to the study of Geometric Optics to high school students.